Identification of CCL19 as a Novel Immune-Related Biomarker in Diabetic Nephropathy - Chen, Hanzhi; Zhang, Zhijian; Zhou, Leting; Cai, Ting; Liu, Bin; Wang, Liang; Yang, Junwei (Frontiers in Genetics, 2022)
Diabetic nephropathy (DN) is one of the major microvascular complications in diabetic patients and the leading cause of end-stage renal disease (ESRD). Previous studies found that immune-related genes and immune cell infiltration play important roles in the pathogenesis and development of DN. Therefore, this study aimed to explore immune-related biomarkers in DN. In this research, three microarray datasets that included 18 DN and 28 healthy tubule samples were downloaded and integrated as the training set to identify differentially expressed immune-related genes (DEIGs). A total of 63 DEIGs were identified, and most upregulated DEIGs were primarily involved in the inflammatory response and chemokine-mediated signaling pathways. The Microenvironment Cell Populations-counter (MCP-counter) algorithm was then used to estimate the abundance of infiltrated immune and stromal cell populations. According to DEIG, weighted gene coexpression network and protein–protein network analyses, CCL19 was identified as the hub immune-related biomarker. Moreover, the upregulated level of CCL19 was confirmed in other independent datasets as well as in in vitro experiments with high glucose. In summary, this study provides novel insights into the pathogenesis of diabetic nephropathy and identifies CCL19 as a potential critical gene of DN.